Isu Radikalisme dan Moderasi Beragama dalam Kebijakan Pendidikan Agama Islam - Hendri Purnama sari; Ida Fitri; Yuniar Yuniar; Indah Wigati (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the issues of radicalism and religious moderation within Islamic Religious Education (PAI) policies and their implementation in learning practices. The research employs a descriptive qualitative approach using a literature study method by examining policy documents, curriculum frameworks, and relevant academic literature. The findings indicate that religious moderation plays a significant preventive role in addressing extreme perspectives in educational settings through the integration of tolerance, balance, and inclusivity values into the curriculum and classroom practices. Teachers’ roles as moderation agents, dialogical and contextual learning models, and adaptive educational policies are key factors in strengthening religious moderation. However, challenges arising from the digital era and social diversity require continuous curriculum development, teacher training, and institutional collaboration to ensure effective implementation